Perception of the presence, impacts and control of the invasive species Sus scrofa in the local community living near the Itatiaia National Park, Brazil - Pereira, Carina Zanco; Rosa, Clarissa Alves; Zanzini, Antônio Carlos (Ethnobiology and Conservation, 2019)
The wild pigs are considered as one of the 100 worse invasive species in the world and they are expanding their rage through Brazilian territory, leading to many social and environmental impacts. Our study’s aim was to estimate the perception of rural communities about the presence of wild pigs in the vicinity of the Itatiaia National Park (INP), Brazil, including the perceived impacts and the acceptance of management policies of the species. We conducted this study in nine rural communities around the INP, where we interviewed 210 inhabitant using structured questionnaires with ten closed dichotomous questions. The majority of respondents know about the existence of the wild pigs in the region and figure out their presence as undesirable and a threaten to the environment and crops, mainly corn, vegetable gardens and sugarcane. Most of respondents are favorable to control measures and eradication of the species, showing one common goal between local community and INP’s managers and an opportunity of effective management of the specie in the region. We reinforce the importance of programs of management of the wild pigs in the region that involves different social actors, including the managers of the INP, farmers and legal hunters properly certified by Brazilian legislation.